Agricultura familiar: sustentabilidade, ator e agência - Toledo, Eliziário Noé Boeira (2019)
The relationship between familie farming and environmental sustainability is very present in the rural development literature. Approaches suggest that this segment of farmers has characteristics, skills and abilities that are friendlier to the use of natural goods and assets while producing food. The dissertation sought to answer the problem: To what extent does the pursuit of monetary income, by exercising the conditions of actor and agent of family farmers, relativize the option for the demands of environmental sustainability? The general goal of this study is to broaden the empirical knowledge about the problems that support the actions and strategies adopted by family farmers, in the income generation of the rural establishment combined with the possibilities of adopting the principles of environmental sustainability. The empirical research was conducted in the counties of Barão do Cotegipe, Sertão and Viadutos, in the Upper Uruguay region, and it was adopted the modality and case study. 54 family farmers were interviewed using closed questionnaires, and the data were formatted by the SPSS software. In addition, 10 qualitative interviews were conducted with experts such as leaders, rural extension technicians, public managers. This study sought to understand if the strategies adopted by farmers in running their properties consider the need to observe the demands of sustainability, understood by the view of family farmers, through the actor-oriented theoretical perspective advocated by Long and Ploeg and the agency, one of the elements of Giddens's Theory of Structuring. The fieldwork showed that it was possible to verify the provenance of the hypothesis that is the low level of interest and investments from farmers in the environmental area, which is independent of income levels, and when this occurs is by imposition of penalties arising from crimes or environmental offenses committed, or by option in investments in the forest saving modality. The hypothesis that family farmers are contrary to environmental legislation has not been confirmed. The data confirmed that the family farmers have a broad and clear understanding of the environmental issues and the effects of farming activities on the environment and even defend the need and importance of the current environmental legislation, despite the finding of significant environmental liabilities in rural establishments detected during the CAR. A significant part of the farmers do not know or do not adequately understand the options offered by “alternative agriculture” in relation to the conventional model of the agricultural package, proving the proposed hypothesis.